Identification of Genetic Modules Mediating the Jekyll and Hyde Interaction of Dinoroseobacter shibae with the Dinoflagellate Prorocentrum minimum - Wang, Hui; Tomasch, Jürgen; Michael, Victoria; Bhuju, Sabin; Jarek, Michael; Petersen, Jörn; Wagner-Döbler, Irene (Frontiers in Microbiology, 2015)
The co-cultivation of the alphaproteobacterium Dinoroseobacter shibae with the dinoflagellate Prorocentrum minimum is characterized by a mutualistic phase followed by a pathogenic phase in which the bacterium kills aging algae. Thus it resembles the “Jekyll-and-Hyde” interaction that has been proposed for other algae and Roseobacter. Here we identified key genetic components of this interaction. Analysis of the transcriptome of D. shibae in co-culture with P. minimum revealed growth phase dependent changes in the expression of quorum sensing (QS), the CtrA phosphorelay, and flagella biosynthesis genes. Deletion of the histidine kinase gene cckA which is part of the CtrA phosphorelay or the flagella genes fliC or flgK resulted in complete lack of growth stimulation of P. minimum in co-culture with the D. shibae mutants. By contrast, pathogenicity was entirely dependent on one of the extrachromosomal elements of D. shibae, the 191 kb plasmid. The data show that flagella and the CtrA phosphorelay are required for establishing mutualism and prove a cell density dependent killing effect of D. shibae on P. minimum which is mediated by an unknown factor encoded on the 191 kb plasmid.